Chemical properties handbook physical thermodynamic, environmental, transport, safety and, health related properties for organic and organic chemicals - Yaws, Carl L (McGraw-Hill handbooks., 1999)
"Accurate information on how chemicals behave at different temperatures and under different conditions is often hard-to-find or difficult to calculate. This unique Handbook provides scientific, engineering, and environmental professionals and students with this necessary information, in an all-in-one, easy-access format." "This handbook covers both organic (C[subscript 1] to C[subscript 28] compounds) and inorganic (Ag to Zn compounds) substances, and provides both experimental values and estimated values based on methods developed by the author and other noted experts."--BOOK JACKET.